Macroalgae may mitigate ocean acidification effects on mussel calcification by increasing pH and its fluctuations. (26th June 2017) - Wahl, M.; Schneider Covachã, S.; Saderne, V.; Hiebenthal, C.; Müller, J. D.; Pansch, C.; Sawall, Y.
Abstract: Ocean acidification (OA) is generally assumed to negatively impact calcification rates of marine organisms. At a local scale however, biological activity of macrophytes may generate pH fluctuations with rates of change that are orders of magnitude larger than the long‐term trend predicted for the open ocean. These fluctuations may in turn impact benthic calcifiers in the vicinity. Combining laboratory, mesocosm and field studies, such interactions between OA, the brown alga Fucus vesiculosus, the sea grass Zostera marina and the blue mussel Mytilus edulis were investigated at spatial scales from decimetres to 100s of meters in the western Baltic. Macrophytes increased the overall mean pH of the habitat by up to 0.3 units relative to macrophyte‐free, but otherwise similar, habitats and imposed diurnal pH fluctuations with amplitudes ranging from 0.3 to more than 1 pH unit. These amplitudes and their impact on mussel calcification tended to increase with increasing macrophyte biomass to bulk water ratio. At the laboratory and mesocosm scales, biogenic pH fluctuations allowed mussels to maintain calcification even under acidified conditions by shifting most of their calcification activity into the daytime when biogenic fluctuations caused by macrophyte activity offered temporal refuge from OA stress. In natural habitats with a low biomass to water body ratio, the impact of biogenic pH fluctuations on mean calcification rates of M. edulis was less pronounced. Thus, in dense algae or seagrass habitats, macrophytes may mitigate OA impact on mussel calcification by raising mean pH and providing temporal refuge from acidification stress.